Pengaruh individu, dukungan keluarga dan sosial budaya terhadap konsumsi makanan ibu muda menyusui (Studi kasus di Desa Sofyan Kecamatan Simeulue Timur Kabupaten Simeulue) - T. M Rafsanjani (AcTion: Aceh Nutrition Journal, 2018)
Food that given to the breastfeeding mother should contain sufficient calories (energy) to replace the energy released as well as the energy needed to produce breast milk. Various factors that influence the mother’s nutrient in the breastfeeding period are lack of knowledge, lack of confident/attitude, also lack family support and environment. This research used an analytical survey with a cross-sectional study approach. The respondents of this research were 34 mothers that also the total of population. Data analysis was performed in univariate and bivariate analysis with the purpose of testing the hypothesis. Then, the method used was the Chi-Square Test (x2) and used the SPSS 17th version. The result would be considered significant if p-value < 0,05. The result of this study shows that there was the influence of individual understanding toward consumption of young breastfeeding mother with p-value 0,003. There was an influence of family support toward consumption of young breastfeeding mother with p-value 0,028. Then, there was an influence of social culture toward consumption of young breastfeeding mother with p-value 0,027. It can be concluded that there was an influence between individual understanding, family support and social culture toward food consumption of young breastfeeding mothers. Midwives and the community are expected to improve the understanding of individual breastfeeding young mothers and the community about nutritional needs during breastfeeding in various ways, including counseling and mentoring.Makanan  yang  diberikan  kepada  ibu  menyusui  harus  mengandung cukup kalori (energi) guna mengganti energi yang dikeluarkan maupun yang dibutuhkan  untuk  menghasilkan  ASI. Berbagai faktor  yang  mempengaruhi  gizi  ibu  pada  masa menyusui,  adalah  kurangnya  pengetahuan  ibu,  kurangnya  rasa percaya diri ibu/sikap, serta kurangnya dukungan keluarga dan lingkungan. Penelitian  ini  bersifat  survey  analitik, pendekatan  cross sectional dengan responden penelitian 34 orang yang merupakan total dari populasi. Analisis data dilakukan dengan analisis univariat dan bivariat dengan tujuan menguji  hipotesis,  dengan menggunakan aplikasi komputer  SPSS  versi 17, dan digunakan uji  Chi-Square  Tets  (x2), dengan kategori bermakna jika p value < 0,05. Hasil  penelitian menunjukkan  bahwa  ada  pengaruh  pemahaman individu terhadap  konsumsi  makanan  ibu muda menyusui dengan p= 0,003, ada pengaruh dukungan keluarga terhadap konsumsi makanan ibu  muda menyusui  dengan nilai p= 0,028, dan ada  pengaruh  sosial budaya terhadap konsumsi  makanan  ibu muda menyusui  dengan nilai p= 0,027.  Dapat disimpulkan bahwa terdapat pengaruh antara pemahaman individu, dukungan keluarga dan sosial budaya terhadap  konsumsi makanan ibu muda menyusui. Diharapkan kepada  Puskesmas, bidan dan masyarakat agar dapat  meningkatkan pemahaman individu ibu muda menyusui dan masyarakat tentang kebutuhan nutrisi pada masa menyusui melalui.